Rediscovery of Youngia longipes reveals a new species of Youngia (Asteraceae) in China - Liu, Qun; Zhang, Ting; Lin, Nan; Zhang, Dai-Gui; Huang, Xian-Han; Yang, Jing-Yuan; Tojiboeva, Umida; Zhang, Jian-Wen; Deng, Tao (Phytotaxa, 2024)
Youngia wulingensis, a new species of Asteraceae from Wuling Mountain, central China, is described and illustrated. This new species had been identified as Y. longipes for a long period of time. However, we rediscovered Y. longipes in its type locality, re-examined the type specimen of Y. longipes, and found out many differences between Y. longipes and Y. wulingensis, which can be easily distinguished by the shape of leaves and especially the cylindrical involucre with a keel-like central rib. The phylogenetic analyses based on the internal transcribed spacers (ITS) and one chloroplast marker (rps16) indicated that three accessions of Y. wulingensis were grouped together (BP = 1 and LP = 0.98) and appeared sister to Y. zhengyiana with strong support (PP = 1, LP = 0.98). Finally, we characterised the new species by morphological comparisons and molecular analyses.